Evolution of a Borrowed Genre in Malay Literature (1922-1941): The Case of Crime Fiction in Malaysia - Kukushkina, Evgeniya S. (SARE: Southeast Asian Review of English, 2020)
Malaysian crime fiction in Malay is still under researched, with the main stages of its development yet to be identified. This article aims to partially close this gap by addressing the period before World War II. The study uses the comparative method, applied synchronically to determine the extent of Western influence on Malay crime fiction at a particular time; and diachronically, to outline the historical evolution of the genre. The analysis demonstrates that in the 1920s, the influence of Western crime fiction resulted in borrowings and imitations of foreign plots. Action took place predominantly abroad and the riddle formed the core of the narrative. In the 1930s, the genre had evolved to depict local realities, and the stories became politically engaged and coloured by Malay nationalism. The focus in the narratives shifted from the riddle to the sociopolitical message of the author. Consequently, by the 1940s, Malay crime fiction rapidly lost its generic features, and this brought about the subsequent decline of the genre in Malaysia.